Perception on sports' involvement among undergraduates of UiTM Seremban / Wan Nur Safia Meor Zainuazni and Rozita Abd Latif - Meor Zainuazni, Wan Nur Safia; Abd Latif, Rozita (Universiti Teknologi MARA, 2020)
Debates on different perception about sports occur because people had their own perception related to sports. This research showed the perception of sports involvement among undergraduates in UiTM Seremban. Quantitative research method used. The forms composed by four batteries of items related to game, training, "champion", and value of sport. The forms measure six concepts of sport: Competition, Education, Fun, Health, Socialization and Participation. Each concept could be measured by mark from zero (not important at all) to five (very important). The respondent was divided into three groups: undergraduates from Faculty of Sports Science and Recreation (FSR), Faculty of Administration Science and Policies (FSPP), Faculty Science Computer and Mathematic (FSKM) in Universiti Teknologi Mara (UiTM) Seremban. 28 undergraduates from three facultyselected through stratified random samplings. Competition was the main aspect of sport. Education, socialization and fun were also important for all. Participation and health are less considered. "It is important for them to win every sporting event that they participate" as most important issues during game. UiTM graduates considered training as participation moment. "Training help to build good body posture" was considered as important things for a champion besides technical skill and honours. The UiTM undergraduates would suggested to practice sport "to get a good skill and techniques that can helped a person to success on the field" as benefit that they can get in joining sports. As the result, the result showed, competition as the main of involvement as perceived.